Lensalyza photography studio reservation system - Ku Mohd Razali, Ku Siti Nor Habibah; Kasim, Shahreen; Hassan, Rohayanti; Mahdin, Hairulnizam; Ramli, Azizul Azhar; Md Fudzee, Mohd Farhan; Salamat, Mohamad Aizi (Zibeline Internasional Publishers, 2018)
Lensalyza Photography Studio is an organization that provides photography reservation service. This company located at strategic area that is students and publics gathered area that they visit to reserve photography like wedding event, engagement, convocation, family portrait and so on. Besides, this company also provides photography reservation service through telephone, social page like Facebook and direct reservation with company. However, Lensalyza studio’s reservation is done manually whereby operators record customer’s information by manual. There are many problems occurred in which overturn of reservation data and manual report generation through file system. The main purpose of this project is to automatize the manual system to web system. In conclusion, this system able to help publics reserve photography easily, faster and accurate and some more facilitate operator’s works in terms of file management system.